2011
DOI: 10.1186/1751-0147-53-52
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic groups and cephalosporin resistance genes of Escherichia coli from diseased food-producing animals in Japan

Abstract: A total of 318 Escherichia coli isolates obtained from different food-producing animals affected with colibacillosis between 2001 and 2006 were subjected to phylogenetic analysis: 72 bovine isolates, 89 poultry isolates and 157 porcine isolates. Overall, the phylogenetic group A was predominant in isolates from cattle (36/72, 50%) and pigs (101/157, 64.3%) whereas groups A (44/89, 49.4%) and D (40/89, 44.9%) were predominant in isolates from poultry. In addition, group B2 was not found among diseased food-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
5
44
3
1
Order By: Relevance
“…These results were almost similar to other studies which demonstrated that the isolates of phylogroup A were prevalent in the intestinal tracts of most animals 24,37 and phylogroup B1 was dominant among isolates from healthy cattle. 38 In accordance with the previous reports in Iran, 23,39 this study showed that the phylogroup B1 was dominant in calves. The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations.…”
Section: Discussionsupporting
confidence: 80%
“…These results were almost similar to other studies which demonstrated that the isolates of phylogroup A were prevalent in the intestinal tracts of most animals 24,37 and phylogroup B1 was dominant among isolates from healthy cattle. 38 In accordance with the previous reports in Iran, 23,39 this study showed that the phylogroup B1 was dominant in calves. The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations.…”
Section: Discussionsupporting
confidence: 80%
“…A few articles are available on detection of ESBL-E. coli from healthy or diseased swine population in Asian countries such as China (Duan et al, 2006;Hu et al, 2013), South Korea (Tamang et al, 2013) and Japan (Asai et al, 2011). In India, mostly exotic breeds of pigs are reared by organized farming and indigenous or non-descript breeds are reared by backyard farming and garbage belts (Banik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Animal bacteria do not persist in human intestinal microflora mainly due to lack of host specificity [38]. In this context, ESBLproducing E. coli isolated from animals can be different from clinical isolates [39]. Moreover, mathematical models of antimicrobial usage in the farm industry and the emergence of drug resistance in humans strongly suggests that infection control and prudent medical antimicrobial usage rather than elimination of the use of antimicrobials in animals will more likely reduce the prevalence of antimicrobial resistance in hospitals.…”
Section: Veterinary Antimicrobial Therapies and Esbl Emergence In Hummentioning
confidence: 99%